Crocin and Quercetin protect HCT116 and HEK293 cells from Zearalenone-induced apoptosis by reducing endoplasmic reticulum stress - Ben Salem, Intidhar (Cell Stress Chaperones, 2015)
Mycotoxins are considered to be significant contaminants of food and animal feed. Zearalenone (ZEN) is a non-steroidal estrogenic mycotoxin produced by several species of Fusarium in cereals and agricultural products. ZEN has been shown to be cytotoxic, genotoxic, and mutagenic in different cell types. In the present study, we investigated the involvement of endoplasmic reticulum (ER) stress in ZEN-mediated toxicity in human intestine (HCT116) and kidney (HEK293) cells and evaluated the effects of the two common dietary compounds Quercetin (QUER) and Crocin (CRO). We show that ZEN treatment induces ER stress and activates the unfolded protein response (UPR) as evidenced by XBP1 mRNA splicing and upregulation of GRP78, ATF4, GADD34, PDIA6, and CHOP. Activation of the ER stress response is associated with activation of the mitochondrial pathway of apoptosis. This apoptotic process is characterized by an increase in ROS generation and lipid peroxidation, a loss of mitochondrial transmembrane potential (ΔΨm), and an activation of caspases and DNA damages. We also demonstrate that the antioxidant properties of QUER and CRO help to prevent ER stress and reduce ZEN-induced apoptosis in HCT116 and HEK293 cells. Our results suggest that antioxidant molecule might be helpful to prevent ZEN-induced ER stress and toxicity.